The Association between Socio - economic Factors and Coronary Artery Disease in Yazd Province: a case - control Study - Mohammad Hasan Lotfi; Fatemeh Amiri; Seyed Khalil Forouzannia; Hossein Fallahzadeh; Haniyeh shekari (Shahid Sadoughi University of Medical Sciences, 2014)
Introduction: One of the strongest and most consistent predictors of morbidity and mortality of an individual is socio -economic status (SES) and coronary artery disease (CAD) is maybe the most prominent disturbance caused by socio-economic inequality. To investigate the relation between socio - economic factors with CAD this study was conducted in Yazd province. Materials and Methods:This retrospective case-control study based on hospital was performed from January 1391 to October 1392 in Yazd province.The total sample size achieved from statistical software was 500 patients (n=250 in case and n=250 in control group). Data were collected using questionnaire (face to face interviews), Laboratory and anthropometric measurements and physical examination.To analyze the results, statistical tests such as chi-square, student T-test and Conditional Multiple Logistic Regression were conducted. Results:Elementary education and total family monthly income 6 member in case group was statistically significantly higher. After checking of simultaneous effect of socio-economic variables in logistic regression model, Elementary education still showed a significant relation (OR=10.462,95%CI:1.68-65.33). Also findings indicate that Families with 700,000-1,000,000 Tomans of monthly income were in lower risk of getting CAD (OR=0.275,95%CI:0.078- 0.97). In addition, the risk of getting CAD in city residents was 9.3 (95%CI:1.220-71.041) times higher than rural's. Conclusions:Overall, it seems that urbanization, poor education and low income can play a role in the causation of CAD Yazd province.So for the prevention of CAD, promoting healthy lifestyles, alleviating poverty, increasing knowledge about CAD risk factors and national policy changes seems to be necessary.